2018
DOI: 10.1002/jso.25237
|View full text |Cite
|
Sign up to set email alerts
|

Lymphedema and concomitant venous comorbidity in the extremity: Comprehensive evaluation, management strategy, and outcomes

Abstract: Backgroud The optimal approaches for concurrent vascular lesions with limb lymphedema are not well established. The purpose of the study was to investigate the outcome of the surgical management of lymphedema with concomitant vascular lesions. Methods Between August 2010 and November 2015, 15 consecutive patients with extremity lymphedema and concomitant vascular lesions treated with vascularized lymph node flaps were reviewed. The patients had vascular interventions discovered during workup for lymphedema sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…Ultrasound Doppler and computed tomography angiography (CTA) were utilized to rule out any proximal vascular lesions and to evaluate the patency of any VLNT for lower-extremity lymphedema. 13 Lymphoscintigraphy was performed, and Taiwan Lymphoscintigraphy Staging was used to interpret findings of partial or total lymphatic obstruction of the lower extremities. 14 Magnetic resonance imaging (MRI) was performed to confirm extravasation of contrast into the peritoneal cavity and to visualize aberrant lymphatic tracts in the soft tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Ultrasound Doppler and computed tomography angiography (CTA) were utilized to rule out any proximal vascular lesions and to evaluate the patency of any VLNT for lower-extremity lymphedema. 13 Lymphoscintigraphy was performed, and Taiwan Lymphoscintigraphy Staging was used to interpret findings of partial or total lymphatic obstruction of the lower extremities. 14 Magnetic resonance imaging (MRI) was performed to confirm extravasation of contrast into the peritoneal cavity and to visualize aberrant lymphatic tracts in the soft tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Qualitatively, most studies reported improved symptoms and QoL. 21,22,57,58,73,74,76 Unsatisfactory results were reported in the patient managed with omentum transposition: the leg swelling initially subsided during the first 6 months postoperatively, but the edema gradually returned as the patient became overweight. The overall complication rate was 13%; these included hematoma formation (n ¼ 1), venous congestion or thrombosis (n ¼ 4), and microsurgical revisions (n ¼ 4).…”
Section: Lymphaticovenous Anastomosismentioning
confidence: 99%
“…Females are affected approximately 3.5‐fold more often than males 2,3 . Primary lymphedema is related to gene mutations, especially genes correlated with the regulation of vascular endothelial growth factor C 4,5 . At least 20 genes have been recognized to be associated with primary lymphedema, and approximately 30% of patients have these genes 4 .…”
Section: Introductionmentioning
confidence: 99%
“…At least 20 genes have been recognized to be associated with primary lymphedema, and approximately 30% of patients have these genes 4 . Primary lymphedema individuals, therefore, often have comorbidities with vascular diseases 4,5 . Furthermore, immune imbalance, such as hyperactivation of CD4 T cells, has been proven to induce lymphedema in primary lymphedema patients 6,7 …”
Section: Introductionmentioning
confidence: 99%